Leading Change in Gender and Diversity in Higher Education from Margins to Mainstream (Edition 1) - CohenMiller, Anna; Hinton-Smith, Tamsin; Samuel, Nupur; Haeri Mazanderani, Fawzia (2022)
This edited book provides international insights and recommendations around topics of gender and diversity in higher education linking to larger societal goals of improving equality. Within each of the four sections - Student recruitment and retention, Student experience, Faculty and staff experiences and culture, and Higher education cultures of teaching and research - topics unpack and speak to gender and diversity, equity, inclusion and access, social justice, and leadership and sustainability in higher education institutions (HEIs). Incorporating innovative processes and methods, the researchers address how the experiences of groups who have been subordinated and marginalized can be heard, proposing a re-imagination of empowerment and leadership within higher education and best practices for the benefit of ongoing higher education development. This book is ideal reading for higher education leaders, students on higher education courses, leadership courses, gender in education, as well as researchers, practitioners, for topics of gender and diversity, equity, inclusion and access, social justice, leadership and sustainability in HEIs.